The importance of psychological services within companies in Iceland : employers views and opinions - Ragnhildur Eir Stefánsdóttir 1995- (2020)
Mental illness affects individuals all around the world and depression is considered to be one of the leading causes of disability in the world. Most of the icelandic people spend a portion of their lives at work and therefore the mental health of the employees must be taken care of. The purpose of this study is to examine the views on offering psychological services within a company, in order to improve the mental health of their employees. This study included a total of (N = 21) individuals where the gender ratio was somewhat equal, with 11 females (52.4%) and 10 male (47.6%) participants. The largest age group in this study were individuals aged 41 years and older (76.2%). Results showed that most participants in this study did not offer medical or psychological services, as most participants felt no need for that kind of service (N = 10). Findings also showed that the age of participants and the number of employees within the company did not result in a worse attitude towards psychological services. Keywords: mental health, psychological services, employees, employers, work environment. Andlegir sjúkdómar hrjá einstaklinga um allan heim og er þunglyndi talin vera ein helsta orsök vangetu við að framkvæma ýmis viðfangsefni, í heiminum. Flestir íslendingar eyða stórum hluta lífs síns við vinnu og þess vegna þarf að passa andlega heilsu starfsmanna. Tilgangur rannsóknarinnar er að skoða álit yfirmanna eða stjórnenda á því að innleiða sálfræðiþjónustu inann fyrirtækis til þess að bæta andlega heilsu starfsmanna. Rannsóknin innihélt samtals (N=21) þátttakanda þar sem kynjahlutfall var fremur jafnt, þar sem konur voru 11 talsins (52,4%), þó örlítið fleiri en karlar sem voru 10 talsins (47,6%). Stærsti aldurshópurinn í þessari rannsókn voru einstaklingar eldri en 41 árs (76,2%). Niðurstöður sýndu að meirihluti þátttakenda buðu starfsmönnum sínum hvorki upp á læknisþjónustu né sálfræðiþjónustu, því flestir þeirra töldu enga þörf á því (N=10). Að sama skapi hafði hvorki aldur þátttakenda né starfsmannafjöldi innan ...